Hole Saw-based Pipe Notcher Design: A Cost-effective Manufacturing Solution for 1–3 inch Diameter Pipe - Suraya Suraya; Frid Forghanjaya; Devi Rahmadhani; Hanifan Fachturrahman; Agus Setiawan (Open Science and Technology, 2026)
Background: The development of the manufacturing industry demands increased efficiency and precision in pipe joining, a crucial process in machine construction. However, a major obstacle in the field is the manual pipe notching process, which is time-consuming and highly dependent on the operator's skill level, often resulting in imprecise cuts. This inconsistent notching directly complicates the pipe joining process by welding.Aims: This research aims to design and produce a portable pipe notcher tool based on a hand drill machine for pipes with a diameter of 1–3 inches to improve the quality of perpendicular pipe joints during welding.Methods: The research method uses a systematic approach which includes needs identification, 3D design planning, manufacturing, and experimental testing.Result: The design resulted in a tool with dimensions of 980x540x385 mm with smoother and more precise cutting results compared to manual methods. Tests showed significant cutting time efficiencies: Ø1 inch pipe was reduced from 205 to 53 seconds, Ø2 inch from 286 to 75 seconds, and Ø3 inch from 484 to 99 seconds.Conclusion: This pipe notcher tool design has been proven to increase productivity and produce precise cuts, providing an affordable, appropriate technology contribution to the small-scale manufacturing industry.